Welcome to another Spore reading group! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The president, Godwin Inedia, and Secretary General, Bright Obaseki, have told us formally 'of the existence of the Spore Reading Group (SRG) in Ambrose Alli University, Ekpoma, Edo state, Nigeria. Its over-riding objectives are to inculcate reading...